Modeling Smart City of Kendari City: Gap Analysis and Strategic Potential - Adris Ade Putra; Muammar Makmur; Siti Nurjanah Ahmad; Riyan Abdillah Takdir (Engineering And Technology Journal, 2024)
Kendari has significant potential to develop into a smart city. Urban infrastructure, such as road networks, public services, and the availability of internet and technology, has improved in recent years. However, the challenges faced in developing a smart city in Kendari cannot be underestimated. Major challenges include limited government budgets, a lack of sectoral integration, and societal resistance to new technologies. Therefore, an approach is needed to develop a region-based smart city model in Kendari, enabling the city to achieve its vision of sustainable development. This study aims to analyze the gap between actual conditions and standard indicators across six dimensions of a smart city in Kendari, identify strengths, weaknesses, opportunities, and threats (SWOT analysis) in smart city development, and provide strategic recommendations to accelerate its implementation. The result of this reserach reveal that Kendari has immense potential to become a smart city but still faces significant challenges in every dimension. Gap analysis indicates that the smart government and smart environment dimensions require priority attention. The SWOT analysis offers strategic directions to leverage strengths and opportunities to address weaknesses and threats.